Simulating performance characteristics of induction motor under a balanced load by direct on-line starting - Stephen Ejiofor, Oti; Cajethan Abuchi, Nwosu; Damian Benneth, Nnadi; Victory, Madueme (International Journal of Engineering and Technology, 2019)
This paper divulges the use of MATLAB simulation model to investigate the performance characteristics of a three-phase induction motor using the Direct on-line (DOL) starting. The induction motor operational characteristics by the DOL scheme during transients and start-up periods and afterwards were investigated. The induction motor parameters and the generated equations were expressly used to create the embedded MATLAB functions which in turn were used to engender the graphs for better comprehension.Â Â